1994
DOI: 10.1007/bf00025601
|View full text |Cite
|
Sign up to set email alerts
|

Seed coat permeability and its inheritance in a forage lupin (Lupinus hispanicus)

Abstract: The species Lupinus hispanicus, through its use as self-seeding forage, can contribute to solve the problem of forage scarcity during the summer in the livestock farming of the central-west Iberian Peninsula. A feature of the highest importance in achieving self-seeding is the seed-coat permeability . An evaluation of this characteristic has been carried out in a Lupinus hispanicus collection from Salamanca (Spain), its inheritance, and the influence of daily temperature fluctuations on the `softening' of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
1
10
1
1
Order By: Relevance
“…One gene (A) is dominant for hardseededness, a second gene (B) is dominant for softseededness when the A locus is homozygous recessive (aa), while the double recessive genotype (aabb) is hardseeded. In Lupinus hispanicus (Arrieta et al 1994), Lupinus angustifolius (Forbes and Wells 1968), and Lupinus luteus (Mikolajczyk 1966), seed-coat permeability is controlled by one recessive gene. However, Serrato-Valenti et al (1989) found that in Lupinus angustifolius, where the micropyle is the port of water entry in soft seeds, permeability is controlled by two genes.…”
Section: Genetics Of Seed-coat Impermeability In Grain Legumesmentioning
confidence: 99%
“…One gene (A) is dominant for hardseededness, a second gene (B) is dominant for softseededness when the A locus is homozygous recessive (aa), while the double recessive genotype (aabb) is hardseeded. In Lupinus hispanicus (Arrieta et al 1994), Lupinus angustifolius (Forbes and Wells 1968), and Lupinus luteus (Mikolajczyk 1966), seed-coat permeability is controlled by one recessive gene. However, Serrato-Valenti et al (1989) found that in Lupinus angustifolius, where the micropyle is the port of water entry in soft seeds, permeability is controlled by two genes.…”
Section: Genetics Of Seed-coat Impermeability In Grain Legumesmentioning
confidence: 99%
“…In forage lupins ( Lupinus spp. ), for instance, a recessive allele has been identified which results in 100% permeable seed proportions at maturity (Arrieta et al , 1994; Boersma et al , 2007). Permeable-seeded lines are also known for Lens (Ladizinsky, 1985), Vicia (Ramsay, 1997) and Ornithopus (Taylor, 2005) but, to our knowledge, not for Trifolium .…”
Section: Discussionmentioning
confidence: 99%
“…En esa decada se hacen los primeros estudios importantes sobre la ganaderfa y la colectivizaci6n ej idal como formas productivas y de organizaci6n social. 18 A partir de la promoci6n y la discusi6n sobre el Plan Chontalpa se hacen los primeros diagn6sticos integrales de lo social sobre este, 19 aunque algunos trabajos irnportantes se publicaran mucho mas tarde, como el de Pedro Arrieta, 20 antes del boom petrolero de los afios setenta, a pesar de un sesgo de privilegio en la alimentacion de los hombres por sabre la de las mujeres. Lo que vino a reforzar (junta con el trabajo anterior de Deweyj.i" la narrativa de los trabajos que defendfan la organizaci6n, las formas de trabajo y la vida campesina sabre las planeaciones racionalizadoras y la petroliza-ci6n social.…”
Section: Ensayo Sociol6gico De Tabasco De 1947 Deunclassified